Time-Dependent Recruitment of Prelimbic Prefrontal Circuits for Retrieval of Fear Memory - Quiñones-Laracuente, Kelvin; Vega-Medina, Alexis; Quirk, Gregory J. (Frontiers in Behavioral Neuroscience, 2021)
The long-lasting nature of fear memories is essential for survival, but the neural circuitry for retrieval of these associations changes with the passage of time. We previously reported a time-dependent shift from prefrontal-amygdalar circuits to prefrontal-thalamic circuits for the retrieval of auditory fear conditioning. However, little is known about the time-dependent changes in the originating site, the prefrontal cortex. Here we monitored the responses of prelimbic (PL) prefrontal neurons to conditioned tones at early (2 hours) vs late (4 days) timepoints following training. Using c-Fos, we find that PL neurons projecting to the amygdala are activated early after learning, but not later, whereas PL neurons projecting to the paraventricular thalamus (PVT) show the opposite pattern. Using unit recording, we find that PL neurons in layer V (the origin of projections to amygdala) showed cue-induced excitation at earlier but not later timepoints, whereas PL neurons in Layer VI (the origin of projections to PVT) showed cue-induced inhibition at later, but not earlier, timepoints, along with an increase in spontaneous firing. Thus, soon after conditioning, there are conditioned excitatory responses in PL layer V. With the passage of time, however, retrieval of fear memories shifts to inhibitory responses in PL layer VI.